Edukasi Pengetahuan “AMINA” (Antianemia) dengan Puding Kelor untuk Pencegahan Anemia pada Ibu Hamil di Posyandu Anggrek, Desa Trimodadi, Kecamatan Abung Selatan, Lampung Utara: Pengabdian - Elsy Juni Andri Kariny; Nadya Dwita Fatma Sari; Apriliana Asih Ratna TD; Apriany Martania; Ayu Lailatul Sanda Dwi Arsita; Desi Ratna Sari; Dety Riyani; Devi Yulianti; Dina Dwi Kurniati; Eka Martini; Ernita Wahyuni; Ersa Maharani; Essy Martha S; Heni Partiwi; Melda Silpia; Neka Okta Farinca; Nita Widayanti; Novia Andriyani; Nova Sapitri; Nurul Hidayah; Ratu Maya Arsila; Reni Anggraeni; Rita Puspitasari; Septi Mulyantini; Septiana Restiyanti; Sevi Aryati; Siti Ifayati; Siti Sangadah; Siti Susanti; Stella Ferlinda; Suryaningsih; Suryi Wulandari; Yusnita Handayani (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Anemia in pregnant women remains a public health problem with a high prevalence. WHO data from 2022 shows that 37% of pregnant women worldwide suffer from anemia, and in Indonesia the figure remains high. In Lampung Province, the prevalence of anemia in pregnant women reached 5.98%, while in Trimodadi Village, North Lampung, 10 out of 25 pregnant women experienced anemia. This condition poses risks to both the mother and the fetus, necessitating prevention through nutrition education and the use of local foods. This community service activity aims to increase pregnant women's knowledge about anemia and introduce moringa pudding as a nutritious local food innovation. The method used was a pretest-posttest on 30 pregnant women at the Anggrek Integrated Health Post (Posyandu) in Trimodadi Village, North Lampung, on October 21, 2025, with data collection through questionnaires, educational leaflets, and a demonstration of making moringa pudding. The results showed a significant increase in knowledge from an average of 50.53 to 78.10 (p-value = 0.000). Therefore, education accompanied by demonstrations is effective in increasing understanding and interest in consuming nutritious local foods and has the potential to be an anemia prevention intervention at the Posyandu level.